PENGARUH BEASISWA TERHADAP PRESTASI BELAJAR SISWA DI SMAIT BUAHATI ISLAMIC SCHOOL - Venni Nabila Farah Muthmainnah; Masduki Ahmad (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to find out the process of selecting the Al-Qur'an Achievement Scholarship Program at SMAIT Buahati, how is the management of the Al-Qur'an Achievement Scholarship Program at SMAIT Buahati, how is the supervision of the Al-Qur'an Achievement Scholarship Program at SMAIT Bauahati. This research method is a qualitative method with data collection techniques through interviews. This research is located at SMAIT Buahati. Source of data comes from primary data and secondary data. The results of this study are that the Al-Qur'an achievement scholarship program at SMAIT Buahati has fully had a major influence on student achievement. The obstacles faced by schools are controlling student memorization every month or every semester reaching 5 juz.